Hubungan Antara Tingkat Kecemasan Dengan Prestasi Akademik Mahasiswa Di Fakultas Psikologi Universitas Muhammadiyah Surakarta - Akbar, Djumadi, Prof. Dr. Mohammad Fanani, dr. Sp. Kj (K), Dr. Erna Herawati, Sp.K.J (2015)
Background: in the academic, anxiety is a psychological attribute that is important. Students often experience anxiety because has a problem like anxiety about academic, stress, depression, problem of associated about society or family, not confident, problem of decisions and suicide. anxiety among college students are closely related with the academic achievemen. Higher level of anxiety contributes to the lower academic achievement of college students. High anxiety level affects the memory performance, decreasing memory, and disrupting concentration while studying Objective: To determinate the relationship between Anxiety and GPA at psychology faculty of Universitas Muhammadiyah Surakarta. Metode: using descriptive analytic methods with cross sectional. total sample are 92 people and then analyze with Pearson Parametric. Result: based on Pearson correlation test was obtained which means Ho is rejected and Ha is accepted because p < 0,001. The Pearson correlation was - 0,655 showed negative correlation with the power of correlation Conclusion: there is significant correlation between anxiety level and academic achievement of college student in Psychology Faculty of Universitas Muhammadiyah Surakarta. The result show that when anxiety increases, academic achievement decreases both in male and female students.